2017
DOI: 10.15740/has/fsrj/8.2/254-259
|View full text |Cite
|
Sign up to set email alerts
|

Tomato pomace as a functional ingredient in cookie making

Abstract: Tomato pomace, a by-product of tomato juice industry, is a rich source of fibre and polyphenols. Also in view of the antioxidant property of pomace, it would play an important role in prevention of diseases. Tomato pomace procured from Food processing training centre (FPTC) SKUAST-K, Shalimar, contained 87.20% moisture, 1.10% ash and 6.20% of dietary fibre. Finely ground tomato pomace was incorporated in wheat flour at 5%, 10%, 15 %, 20% and 25% levels for development of cookies. Water absorption increased sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…It is worth noting that this extensive range of ideas is only possible because different tomato pomaces are used in the research. For example, as in our case, the use of a tomato pomace has been proposed for the preparation of different bakery products, including muffins (Mehta et al, 2018) and cookies (Bhat et al, 2017). In their studies, tomato pomace was obtained in the laboratory and had different compositions.…”
Section: Final Considerationsmentioning
confidence: 98%
“…It is worth noting that this extensive range of ideas is only possible because different tomato pomaces are used in the research. For example, as in our case, the use of a tomato pomace has been proposed for the preparation of different bakery products, including muffins (Mehta et al, 2018) and cookies (Bhat et al, 2017). In their studies, tomato pomace was obtained in the laboratory and had different compositions.…”
Section: Final Considerationsmentioning
confidence: 98%
“…It has to be stressed, however, that the incorporation of even the lowest TP amount (4%) caused a significant reduction ( p < 0.05) in volume and specific volume. Bhat and Ahsan [ 42 ], Chung [ 43 ], and Bhat et al [ 44 ] observed that adding more than 5% TP in biscuits significantly changed the diameter and thickness, probably because the higher TP fibre content diminished gas retention. A volume reduction was expected, because the wheat flour (rich in gluten, responsible for leavened products’ volume) was replaced by the gluten-free TP.…”
Section: Resultsmentioning
confidence: 99%